2021
DOI: 10.1186/s40959-020-00080-w
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare disparities in cardio oncology: patients receive same level of surveillance regardless of race at a safety net hospital

Abstract: Background Cardiotoxicity remains a dreaded complication for patients undergoing chemotherapy with human epidermal growth factor (HER)-2 receptor antagonists and anthracyclines. Though many studies have looked at racial disparities in heart failure patients, minimal data is present for the cardio-oncology population. Methods We queried the echocardiogram database at a safety net hospital, defined by a high proportion of patients with Medicaid or no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Yet, a recent study of 149 patients (68 Black, 41 White, 33 Hispanic) from a safety net hospital who had undergone HER2-targeted therapy or anthracyclines for breast cancer found no statistical difference in the percentage of patients who had surveillance imaging to monitor for a reduction in LVEF. 95 These patients had been referred to a cardio-oncology clinic for cardiovascular care, suggesting a referral pattern with meticulous serial imaging and biomarker follow-up assessments that might benefit disparities in care.…”
Section: Use and Role Of Cardiac Imaging To Reduce Disparities In Car...mentioning
confidence: 99%
“…Yet, a recent study of 149 patients (68 Black, 41 White, 33 Hispanic) from a safety net hospital who had undergone HER2-targeted therapy or anthracyclines for breast cancer found no statistical difference in the percentage of patients who had surveillance imaging to monitor for a reduction in LVEF. 95 These patients had been referred to a cardio-oncology clinic for cardiovascular care, suggesting a referral pattern with meticulous serial imaging and biomarker follow-up assessments that might benefit disparities in care.…”
Section: Use and Role Of Cardiac Imaging To Reduce Disparities In Car...mentioning
confidence: 99%
“…A recent study of 149 patients at a safety net hospital undergoing chemotherapy with trastuzumab and/or doxorubicin with 46% Blacks, 27.5% Whites, and 22% Hispanics reported that all populations received the same level of surveillance and treatment, leading to similar outcomes for cardiotoxicity regardless of the race even though White patients were more likely to live in high-income areas [ 30 ]. Thus, it is possible to attain equitable outcomes even in underprivileged populations with accessible healthcare.…”
Section: Disparities In Healthcare Access and Qualitymentioning
confidence: 99%
“…A retrospective analysis of 149 patients who received human epidermal growth factor receptor 2 ( HER2) receptor antagonists and/or anthracyclines showed lower rates of referrals among patients belonging to areas associated with lower income quartiles. 8 Access to cardio-oncology services is restricted by factors such as lack of funding and infrastructure. Most cardio-oncology clinics are limited to larger institutions that patients with relatively poorer socioeconomic backgrounds may not have access to.…”
mentioning
confidence: 99%